Fashion marketing and trends of competitive differentiation of the brands (ModaPalavra e-periódico, 2015)
Marketing has an important strategic role in leveraging a brand, a product or boost customer loyalty, and it remains reliable in the fashion market for many years. However, with the development of new organizations it has also increased competition in the industry, requiring greater disclosure, creativity and innovation. This article presents a discussion of the new marketing techniques currently used to leverage a company in this industry, its evolution over the years and trends for the future of fashion.
Keywords: fashion; marketing; strategy; innovation; creative economy